2015
DOI: 10.1007/s10704-015-0039-9
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of graphene: a review

Abstract: Fracture is one of the most prominent concerns for large scale applications of graphene. In this paper, we review some of the recent progresses in experimental and theoretical studies on the fracture behaviors of graphene, with discussions touching theoretical strength, mode I fracture toughness, mixed mode fracture, chemical fracture, irradiation fracture, dynamic fracture, impact fracture, and sonication fracture. In spite of rapid developments in experiments and simulations, there are still significant yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(86 citation statements)
references
References 226 publications
(280 reference statements)
5
81
0
Order By: Relevance
“…In this section, we present a brief overview of some recent studies on strength and toughness of 2D materials. A more complete review of this subject on graphene can be found in [16].…”
Section: Strength and Toughnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In this section, we present a brief overview of some recent studies on strength and toughness of 2D materials. A more complete review of this subject on graphene can be found in [16].…”
Section: Strength and Toughnessmentioning
confidence: 99%
“…The strength of a pristine 2D material is usually high [4,6], but it could vary substantially due to the presence of topological defects and out-of-plane deformation [13,14]. The fracture toughness of graphene obtained from experiments is relatively low [15], for which potential toughening mechanisms have been explored [16]. Fundamental questions have also been raised on the appropriate definition of fracture toughness for 2D materials based on fracture mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…39] and fractured graphene [16,19,22,26,40]. AIREBO abilities to describe quite well, both the structure and mechanical properties of graphene, as well as C-C bond breaking and bond formation, makes it a good choice for the study of self-tearing and self-folding of graphene nanoribbons.…”
Section: System Modelmentioning
confidence: 99%
“…Graphene with defects is well-known to be mechanically weaker than pristine graphene. 31 Initially, wrinkles are generated from the mismatch of the thermal expansion coefficient of the copper substrate and that of the graphene 38 during the cooling step of graphene synthesis. Defects along wrinkles may be generated during the chemical vapor deposition process, or during the transfer of graphene to PCTEM, that is, copper etching, mechanical pressing, membrane rinse, and membrane drying.…”
Section: Nano Lettersmentioning
confidence: 99%